Virtually No Effect? Different Uses of Classroom Computers and their Effect on Student Achievement - Oliver Falck; Constantin Mang; Ludger Woessmann (Center for Economic Studies and ifo Institute (CESifo), 2015)
Most studies find little to no effect of classroom computers on student achievement. We suggest that this null effect may combine positive effects of computer uses without equivalently effective alternative traditional teaching practices and negative effects of uses that substitute more effective teaching practices. Our correlated random effects models exploit within-student between-subject variation in different computer uses in the international TIMSS test. We find positive effects of using computers to look up information and negative effects of using computers to practice skills, resulting in overall null effects. Effects are larger for high-SES students and mostly confined to developed countries.
Keywords: I21; I28; 330; computers; teaching; methods; student achievement; TIMSS